Iterative signal separation based multiple phase estimation in digital holographic interferometry - Kulkarni, Rishikesh; Rastogi, Pramod (Optics express, 2015)
We propose a new method for signal separation from a multicomponent interference field recorded in a digital holographic interferometry setup. The setup consisting of multiple object illuminating beams results in an interference field containing multiple signal components. The proposed method utilizes an amplitude discrimination criteria established by setting different intensities to the object illuminating beams in order to separate the signal components iteratively. The signal separation is performed in a small block of the interference field at a time. The augmentation of the block matrix with its own rows and columns is performed which has an effect of noise subspace inflation. This operation offers an improved noise robustness to the signal separation capability of the proposed method. The simulation and experimental results are provided to substantiate the applicability of the proposed method in multidimensional deformation measurement.